Translation of therapeutic strategies to modulate B cell reponses from non-human primate models to human kidney transplantation - Knechtle, Stuart; Kwun, Jean; Song, Shengli; Jackson, Annette; Williams, Kitza; Sanoff, Scott (Frontiers in Transplantation, 2023)
Using novel drugs targeting lymphocyte costimulation, cytokines, antibody, complement, and plasma cells, we have developed strategies in a non-human primate model to modulate the B cell response to incompatible kidney transplants. After more than two decades of research supported by mechanistic studies, this has resulted in clinically relevant approaches that are currently enrolling in clinical trials or preparing for such. In this manner, we aim to address the problems of HLA sensitization for very highly sensitized patients awaiting transplantation and the unmet need of effective treatment for antibody-mediated rejection